Design of a Web-Based New Student Admission Information System Accompanied by a Midtrans Payment Gateway Payment Method at SMP PGRI 16 Sidoarjo - Diky Chandra Ramadhan; Mochammad Alfan Rosid (Procedia of Engineering and Life Science, 2022)
SMP PGRI 16 Sidoarjo is an educational unit with junior high school level with NPSN number 20501661 which has private status and is under the auspices of the Ministry of Education and Culture. SMP PGRI 16 Sidoarjo has its address at Jl. Raden Patah No. 91 E, Pucang Anom, Sidoarjo District, Sidoarjo Regency, East Java Province with postal code 61217. The problem that is owned by SMP PGRI 16 Sidoarjo is at the time of PPDB implementation, where implementation still takes a long time and requires extra energy for the committee in accepting new students. Starting with students having to come to school to queue for taking forms and filling out the forms provided. In addition, announcement information for prospective students is placed on the bulletin board, so that information may not be fully received by prospective students. For prospective students who have been declared graduated by the student body, prospective students will return to school and make payments offline. And for the process of accepting prospective students using conventional, namely using special notes and processing student data using the Microsoft Excel application, so that data processing of prospective students takes a long time and is not integrated with each other. Therefore, in this study, it is proposed to make a web-based application for Admission of New Students. It is hoped that it can help the registration process for new students, so that prospective participants do not need to come to school again. Starting from registration, payment of prospective students who have passed and filling out forms are all done online so that it can simplify and shorten the time for new students.